Near-atomic scale chemical analysis of interfaces in a La(Fe, Mn, Si)13-based magnetocaloric material. (February 2023) - Wang, Siyang; Douglas, James O.; Lovell, Edmund; Wilson, Neil; Guo, Liya; Gault, Baptiste; Ryan, Mary P.; Giuliani, Finn
Abstract: La(Fe, Mn, Si)13 -based magnetocaloric materials are one of the most promising material families for the realisation of near-room temperature magnetic refrigeration. The functional and mechanical properties of these materials crucially depend on their chemistry, which is difficult to control at interfaces between microstructural units. Atom probe tomography was employed to reveal the local elemental distribution at the α-Fe/1:13 phase boundary and the 1:13/1:13 grain boundary. Strong Mn segregation (and Fe depletion) at the α-Fe/1:13 phase boundary suggests the potential effect of phase boundary area on the Curie temperature of the material. A local off-1:13 stoichiometry layer at the 1:13/1:13 grain boundary may adversely affect the magnetocaloric performance. Routes to mitigate the negative effects of interfaces on the functional and mechanical performance of these materials are discussed, in order to achieve durable and efficient operation of magnetic cooling devices. Graphical abstract: Image, graphical abstract